Cognitive Effect of Levetiracetam in Patients with Alzheimer’s Disease or Mild Cognitive Impairment: A Systematic Review - Mohamad Hosein Mohamadi, MD; Amir Bavafa, PhD; Sahar Salehi, PhD; Mahsa Abedi, MSc; Fahimeh Shahabi, MSc; Sana Jafarlou, MD; Pirhossein Kolivand, PhD; Sajad Sahab-Negah, PhD (Current Therapeutic Research)
ABSTRACT: Background: Various therapeutic interventions have been investigated for cognitive impairment, a common problem in Alzheimer’s disease (AD). Levetiracetam (LEV), an antiepileptic drug, has been shown to alleviate cognitive impairment. Objective: The present systematic review aimed to evaluate the cognitive effects of LEV in patients with AD or mild cognitive impairment (MCI). Methods: We searched PubMed/MEDLINE, Scopus, Web of Sciences, and Embase databases for all studies on LEV and cognitive impairment. After multistep screening, we identified qualified interventional studies and performed further data extraction. We reviewed the methodological diversity across the studies and assessed the quality of each study using the critical appraisal of the Joanna Briggs Institute checklist (the risk of bias assessment). Results: Of the 1091 publications, only 5 articles were qualified for review. All studies enrolled patients with AD or MCI, and at least 1 arm of the trial involved LEV therapy. Four of 5 studies reported significant cognitive improvement in patients with AD or MCI after the LEV trials, whereas 1 study found no significant change in cognitive status. The risk of bias assessment revealed that 4 studies had a low risk of bias. Among them, 3 showed significant improvement, whereas 1 did not report a significant change in cognitive function. Conclusions: The efficacy of LEV therapy for cognitive impairment varies across studies owing to different methodologies, dosages, treatment durations, and outcome assessment tools. This study suggests that LEV may exert a beneficial impact on cognitive function in patients with AD or MCI. However, a quantitative comparison or meta-analysis is essential to draw definitive conclusions about the cognitive effects of LEV in AD and MCI.